Auditing : an integrated approach - Arens, Alvin A.; Loebbecke, James K. (Englewood Cliffs, N.J. : Prentice-Hall, 1976)
This book is an introduction to auditing for students who have not had significant experience in auditing. It reflects the changes in information technology, incorporates in-text Internet references, and features material on assurance services.
Includes index.
ucj 18/01/2019
Loans
Keywords: Auditing